MODERN COMPUTER TECHNOLOGIES IN ADOLESCENT CARDIAC SURGERY: A STEP INTO THE FUTURE - Gulnoza Ollomurodovna Muminjonova; Sanjarbek Anvarovich Atakhanov (Web of Journals Publishing, 2025)
Modern medicine is experiencing rapid development, with one of the most significant and innovative fields being cardiac surgery. Cardiovascular diseases, especially congenital heart defects (CHD), pose a serious threat to the adolescent population, requiring high-precision diagnostics and timely surgical intervention. In recent years, the extensive implementation of computer technologies in cardiac surgery has led to significant improvements in treatment efficiency. The use of artificial intelligence, 3D visualization, robotic surgical systems, and the Internet of Things (IoT) not only enhances diagnostic accuracy but also minimizes the invasiveness of procedures, making surgeries less traumatic and safer. The purpose of this study is to examine key technological advancements in adolescent cardiac surgery, analyze their impact on clinical practice, and explore prospects for further development in this field.
Keywords: Cardiac surgery, adolescents, computer technology, competitive systems, 3D visualization, artificial intelligence.